Antagonisme Bakteri terhadap Kapang Patogen pada Lahan Pertanian Tomat di Kabupaten Malang - Mustaqim Mustaqim; Muhammad Fahrurrizal A.; Dasriani Dasriani; Hanifah Rahmawati; Putri Dhamira (Indonesian Journal of Fundamental Sciences, 2020)
Efforts in overcoming the problem of pathogenic mold attack can be done with the use of bacteria. This study aims to isolate the bacteria potentially controlling pathogenic molds in tomato plants (Solanum lycoperscium), as well as to identify potential bacteria controlling pathogenic fungi in tomato plants (Solanum lycoperscium) in Malang Regency. This research is an experimental laboratory study with a randomized block design (RCBD). This study used a Randomized Block Design because the experimental unit used was heterogeneous originating from 3 different locations. Of the 20 types of bacterial isolates, there are 6 bacteria that have the potential to inhibit the growth of Fusarium solani fungi that cause wilt disease in tomato plants, namely labeled bacteria EK, IK, BK, KK, CK and OK. There are six colonies that can act as antagonists of the fungus F. solani. It can be estimated that the six bacteria have the power to remodel and use carbon compounds. The carbon compounds such as arabinosa, xylosa, dextrose, cellobinosa, maltose, mannitol, sorbitol, and the use of citrate.